Rate and capacity of cation release from ultramafic mine tailings for carbon capture and storage - Lu, Xueya; Carroll, Kate J.; Turvey, Connor C.; Dipple, Gregory M. (Applied geochemistry, 2022)
Solid wastes produced during hard-rock mining have capacity to capture and store atmospheric CO2 via dissolution and precipitation of Mg-bearing carbonate minerals. However, there is a discrepancy in our understanding of weathering and dissolution in these wastes, with dissolution and reaction rates in field studies exceeding those predicted by experiments under far-from-equilibrium conditions. To reconcile these differences, a series of flow-through dissolution experiments at 25 °C and 1atm were performed to investigate the short-term dissolution kinetics of ultramafic tailings and minerals. Results show that mineral and tailings samples have two stages of dissolution: a fast, transient (or labile) stage, and a slow, stoichiometric stage. Fast releasing labile cations (i.e. labile Mg2+) are sourced from trace minerals with a high reaction rate (e.g. brucite) and from non-stoichiometric surface reaction processes of major minerals (e.g. serpentine). These cations are missing from most geochemical models for mineral weathering. The implication of these results is that the initial transient dissolution of minerals, which is typically ignored during geochemical investigations into bulk dissolution rates, is the missing ingredient for understanding dissolution of mine tailings. Labile cations released during the initial transient dissolution process have value for rapid and low-cost carbon capture and storage techniques as they represent reactivity, capacity, and the best opportunities to deploy low-cost carbon sequestration techniques using mine tailings and other industrial wastes. The presence of labile cations and changing reaction rates over time may also suggest that short-term reactivity examined during field tests may overestimate long-term carbon capture potential of some sites. •Dissolution tests demonstrate ultramafic minerals and tailings have a fast dissolution stage before reaching stochiometric..•Readily leachable, loosely bounded cations, termed “labile cations” represents rate and capacity of mineral carbonation.•Mineral carbonation capacity of serpentine exceeds that of olivine.•Labile cations suggest reactivity examined during short-term field tests may overestimate long-term carbon capture potential.